Protective Effects of L-Malate against Myocardial Ischemia/Reperfusion Injury in Rats. (31st January 2016) - Ding, Shiao; Yang, Yang; Mei, Ju
Abstract : Objective . To investigate the protective effects of L-malate against myocardial ischemia/reperfusion (I/R) injury in rats. Methods . Male Sprague-Dawley rats were randomly assigned to the following groups: sham (sham), an ischemia/reperfusion (I/R) model group (model), an DMF pretreated group (DMF), and 5 L-malate pretreated groups (15, 60, 120, 240, or 480 mg/kg, gavage) before inducing myocardial ischemia. Plasma LDH, cTn-I, TNF-α, hs-CRP, SOD, and GSH-PX were measured 3 h later I/R. Areas of myocardial infarction were measured; hemodynamic parameters during I/R were recorded. Hearts were harvested and Western blot was used to quantify Nrf2, Keap1, HO-1, and NQO-1 expression in the myocardium. Results . L-malate significantly reduced LDH and cTn-I release, reduced myocardial infarct size, inhibited expression of inflammatory cytokines, and partially preserved heart function, as well as increasing antioxidant activity after myocardial I/R injury. Western blot confirmed that L-malate reduced Kelch-like ECH-associated protein 1 in ischemic myocardial tissue, upregulated expression of Nrf2 and Nrf2 nuclear translocation, and increased expression of heme oxygenase-1 and NAD(P)H:quinone oxidoreductase 1, which are major targets of Nrf2. Conclusions . L-malate may protect against myocardial I/R injury in rats and this may be associated with activation of the Nrf2/Keap1 antioxidant pathway.